Atypical neurological symptoms at high altitude: a systematic literature review - Wiktor Łagowski; Olga Grodzka; Izabela Domitrz (Travel Medicine and Infectious Disease)
Background: Acute Mountain Sickness (AMS) is a prevalent and potentially debilitating condition affecting individuals who participate in high-altitude journeys, mostly above 2500 m. The main symptoms of AMS, listed in the Lake Louise Symptom score used to diagnose AMS, are headache, dizziness, nausea, and fatigue. However, mountaineering can also be associated with other neurological disturbances. Most records related to neurological disorders associated with high-altitude medicine focus on AMS and its typical neurological symptoms indicated in official criteria. Other conditions related to acute exposure to high altitudes are high-altitude headaches (HAH), which usually precede AMS and high-altitude cerebral oedema (HACE), which can be a complication of AMS or appear independently. Methods: This review aimed to describe studies that included atypical neurological symptoms, which appear during acute exposure to high altitudes and are not mentioned in the criteria of AMS or HACE. Four databases, PubMed, Embase, Web of Science, and Medline Ultimate, were screened. PROSPERO registration ID for this review is CRD420250654251. Findings: Studies that met our inclusion criteria presented symptoms related to well-known conditions, such as stroke, deep cerebral vein thrombosis, seizures, or transient neurological dysfunctions. Moreover, cranial nerve palsies, olfactory threshold impairment, multiple sclerosis worsening, or speech, memory, and sensation disturbances were described in patients at high altitudes. Conclusions: This review shows that high altitude may be an inducing factor in other neurological disturbances besides AMS, HAH, and HACE symptoms. The growing popularity of high-altitude stays should be associated with increasing knowledge about the unusual neurological symptoms that may occur.